Improving Patient–Provider Communication and Therapeutic Practice Through Better Integration of Electronic Health Records in the Exam Room: A Pilot Study. (June 2019) - Patel, Minal R.; Smith, Alyssa; Leo, Harvey; Hao, Wei; Zheng, Kai
Background . The rapid proliferation of electronic health records (EHRs) in clinics has had mixed impact on patient-centered communication, yet few evaluated interventions exist to train practicing providers in communication practices. Aims . We extended the evidence-based Physician Asthma Care Education (PACE) program with EHR-specific communication strategies, and tested whether training providers with the extended program (EHR-PACE) would improve provider and patient perceptions of provider communication skills and asthma outcomes of patients. Method . A pilot randomized design was used to compare EHR-PACE with usual care. Participants were providers ( n = 18) and their adult patients with persistent asthma ( n = 126). Outcomes were assessed at baseline and 3- and 6-month postintervention, including patient perception of their provider's communication skills and provider confidence in using EHRs during clinical encounters. Results . Compared with the control group, providers who completed the EHR-PACE program reported significant improvements at 3-month follow-up in their confidence with asthma counseling practices (estimate 0.90, standard error [ SE ] 0.4); p < .05) and EHR-specific communication practices (estimate 2.3, SE 0.8; p < .01), and at 6-month follow-up, a significant decrease in perception that the computer interferes with the patient–provider relationship (estimate −1.0, SE 0.3; p < .01). No significant changes were observed in patient asthma outcomes or their perception of their provider's communication skills. Discussion . Training providers with skills to accommodate EHR use in the exam room increases provider confidence and their perceived skills in maintaining patient-centered communications in the short term. Conclusion . Evidence-supported training initiatives that can increase capacity of busy providers to manage increased computing demands shows promise. More research is needed to fully evaluate EHR-PACE on patients' health status and their perceptions of their provider's care through a large-scale trial.